2016
DOI: 10.1007/s00330-016-4467-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of MR Arthrography with Anterior Trans-Subscapularis versus Posterior Injection Approach for Subscapularis Tendon Tears at 3.0T

Abstract: • Anterior trans-subscapularis and posterior approaches showed no significant difference for SCT tears • Intratendinous collection of gadolinium is more frequent in anterior trans-subscapularis approach • Extent of SCT tears tends to be overestimated in anterior trans-subscapularis approach • Posterior approach should be considered for diagnosing SCT tear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…7,19,71,94,125,144 The anatomic resolution is good, subtle defects can be depicted by contrast material, and leakage of contrast agents is usually evident, thus enhancing the diagnostic accuracy of FT tears. 26,60,68,120 We found that MRA was also the most accurate method for detecting RCTs regardless of type (FT or PT tear). However, the injection of a contrast agent is an invasive procedure, infections and adverse reactions occur, 44 and the examination time is longer.…”
Section: Discussionmentioning
confidence: 77%
“…7,19,71,94,125,144 The anatomic resolution is good, subtle defects can be depicted by contrast material, and leakage of contrast agents is usually evident, thus enhancing the diagnostic accuracy of FT tears. 26,60,68,120 We found that MRA was also the most accurate method for detecting RCTs regardless of type (FT or PT tear). However, the injection of a contrast agent is an invasive procedure, infections and adverse reactions occur, 44 and the examination time is longer.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, another meta-analysis included 14 studies involving 1216 patients with labral lesions, revealed that MRA had the highest sensitivity and speci city compared with those of MRI and CTA, which indicated that MRA was suggested for use in patients with chronic shoulder symptoms or a pathologic abnormality [32]. MRA has a good diagnostic performance mainly depending on the objective evidence of the leakage of contrast agent, accompanied by a good anatomic resolution and subtle defects depicted by contrast agents [33,34]. Nonetheless, MRA, as an invasive diagnosis modality, has many disadvantages and limitations, including a longer examination time, increased risk of infection and adverse complication [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MRA has also the most accurate to detecting the labral lesions of shoulder [48, 49]. The reason that MRA has a good diagnostic value in the detection of full-thickness RCTs is because the objective evidence of the leakage of contrast agent is accompanied by a good anatomic resolution and subtle defects depicted by contrast agents [50, 51]. However, MRA, usually with a longer examination time, will bring the infections and adverse complications because of an invasive procedure of the injection of contrast agent [52].…”
Section: Discussionmentioning
confidence: 99%